The heart of public interventions in historic cities: reflections on the HRIDAY scheme - Swapna Kothari; Shivangi Thakur (Ochrona Dziedzictwa Kulturowego)
This article discusses two specific implementations from the Heritage City Development and Augmentation Yojana, also known as the HRIDAY scheme in India, specifically how they address public spaces in historical cities. HRIDAY (2014-2019) was formulated to provide holistic development and improve infrastructure, mainly in pilgrim towns, under the Ministry of Urban Development, now the Ministry of Housing and Urban Affairs (MoHUA). The scheme took into consideration the complexity of dealing with entire historic cities. This is especially challenging for local urban bodies focused primarily on the core of a city, i.e. its historic centre. The goal was to revitalise the city’s unique character by “encouraging the development of an aesthetically appealing, accessible, informative and secure environment” (MOUD 2015). However, while the scheme ended, there are still many historic towns and cities across the country that could benefit from reflections and insights from already executed projects. To undertake any further development in line with the scheme, it is imperative to understand its application, specifically in terms of public space typology. HRIDAY primarily addressed the need to foster cultural identity by improving public infrastructure and promoting tourism. The article addresses how public chowks (squares) and market streets benefited from the scheme, basing on secondary sources about two selected cities. Discussion covers additions of sanitation and public conveniences, development of venues for cultural events in existing public space and interventions such as creation of interpretation centres and improvement of paths. These analyses serve as the basis for the formulation of guidelines and theories that could inform future heritage development in sensitive urban spaces in cities and towns across India.